Commentary on "Building capable environments using practice leadership". Issue 1 (2nd February 2021) - Jones, Edwin
Abstract : Purpose: This paper aims to present a conceptual viewpoint highlighting the utility of active support in implementing capable environments and to extend this by presenting a three-tiered preventative model of positive behavioural support (PBS) in UK health and social care. Design/methodology/approach: Provision of a commentary on "Building capable environments using practice leadership" by Linda Hume, Nadia Khan and Martin Reilly. Findings: Capable environments and active support should be key, universal and essential PBS tier one supports in UK health and social care. Training staff in Active Support and developing practice leadership help implement capable environments. Originality/value: The three-tiered PBS model was recently proposed by Leitch et al. (2020) and is worthy of further debate and refinement with the involvement of stakeholders. It has several practical implications including refocussing efforts on early intervention to get tier one supports implemented effectively in recognition that PBS is much wider than intense tier three supports. It could reinforce and motivate existing providers of quality support and indicate where and how other providers can commence the process of implementing PBS. Future research could consider the effectiveness of applying implementation science to the field of learning disabilities and PBS in particular.